MENGOPTIMALKAN KEUNTUNGAN : STRATEGI MATEMATIKA BISNIS UNTUK PERTUMBUHAN BERKELANJUTAN - Sulaeman; Selvy Afrioza (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
This study aims to explore and identify effective business strategies for optimizing profits while ensuring sustainable growth. In the context of increasingly competitive markets and pressing environmental challenges, companies need to develop approaches that not only maximize profit but also consider the long-term impact on the environment and society. This research adopts a mixed-methods approach, including quantitative analysis of financial data and case studies from various industries. Findings indicate that the implementation of strategies based on innovation, operational efficiency, and corporate social responsibility (CSR) can significantly enhance profitability and support sustainable growth. The study also identifies best practices and key challenges in the implementation of these strategies, providing valuable insights for managers and policymakers in designing holistic and future-oriented business plans. The results are expected to offer practical guidance for companies aiming to achieve a balance between short-term profits and long-term sustainability.